Influence of the size and weight of the pineapple slips on the fruit development and quality - Gadêlha, Ricardo S. Sarmento; Vasconcellos, Hélio de Oliveira (Pesquisa Agropecuaria Brasileira, 2014)
The purpose of this work was to study the influence of the size and weight of the pineapple slips on its development and fruit quality. Four treatments were tested: A) Slips with 50-55 cm length and 185-200g weight; B) slips with 40-45 cm length and 135-150 g weight; C) slips with 30-35 cm length and 85-100 g weight; D) slips with 20-25cm length and 55-70g weight. The best results were obtained from slips with 50-55cm length and 185-200g weight with a high statistical significance to the following characteristics: plant highness, leaf number, crown weight, slips number and crown size. Slips with 20-25 cm length and 55-70 g weight (D), slips with 50-55cm length and 185-200g weight (A), and slips with 40-45 cm length and 135-150 g weight (B) were in the first group according to crown weight and crown size. About fruit quality there was a high significant difference. The best results in diameter, size, weight and pith diameter were obtained from the slips having 50-55 cm length and 185-200g weight (A). There was no significant difference to juice percentage, total acidity and total solids solubles. Plants from slips with 50-55 cm length and 185-200g weight showed early production in a 534-day cycle from the planting time to flowering.